A survey on hygienic and physicochemical properties of Istrian cheese - Andrea Skelin; Dubravka Samaržija; Sulejman Redžepović; Samir Kalit; Mirna Mrkonjić Fuka; Višnja Magdić; Jasmina Havranek (Mljekarstvo)
Istrian cheese is the traditional hard cheese produced exclusively from the raw milk of the autochthonous Istrian sheep. The aim of this study was to determine the bacteriological quality, physicochemical properties of the sheep milk and Istrian cheese as well as proteolysis of cheese produced on six family farms during the cheese ripening. The hygienic microbial indicators of the sheep milk were poor in comparison to the other East Adriatic regions. However, the number of bacterial indicators rapidly declined during the ripening and they were under the detection limit for “ready to consume” cheese and therefore indicated their good bacteriological quality. Regression function of the effects of the ripening time on physicochemical properties of Istrian cheese during ripening showed a substantial increase in total solids, in salt, in moisture and in salt content as well as in the lactic acid in the total solids. However, these changes were not significant due to the high variability of the Istrian cheese production. The farm cheese making procedure affected the electrophoretic profile of the primary proteolysis in the cheese samples. Significant (P<0.01) increase of the index beta was found due to the high content of salt in moisture (>5 %). Equal degradation of as1-casein and ß-casein during ripening of Istrian cheese occurred. A low percentage of nitrogen fractions soluble in water and in 12 % trichloroacetic acid were determined.